2018
DOI: 10.1080/17429145.2018.1491067
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid improves the tolerance of wheat plants to lead toxicity

Abstract: Among the heavy metals (HMs), lead (Pb) is considered as a toxic HM which adversely affects growth and development of crop plants. The present experiment was aimed to investigate the potential role of ascorbic acid (ASC) in the reversal of Pb-inhibited nitrogen and sulfur assimilation enzymes activity and activity of photosynthesis enzyme ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) and growth response in wheat plants. Wheat seedlings were subjected to 0 mM (control) and 0.2 mM and 0.6 mM of ASC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 61 publications
6
36
0
1
Order By: Relevance
“…Alamri et al [196] investigated the potentiality of exogenous AsA to remove the metal-induced oxidative stress in T. aestivum . They observed that AsA suppressed the higher content of MDA and H 2 O 2 in Pb exposed seedlings by improving the antioxidant enzymes activities, including SOD, CAT, and GR.…”
Section: Exogenous Use Of Asa and Gsh In Conferring Abiotic Stressmentioning
confidence: 99%
“…Alamri et al [196] investigated the potentiality of exogenous AsA to remove the metal-induced oxidative stress in T. aestivum . They observed that AsA suppressed the higher content of MDA and H 2 O 2 in Pb exposed seedlings by improving the antioxidant enzymes activities, including SOD, CAT, and GR.…”
Section: Exogenous Use Of Asa and Gsh In Conferring Abiotic Stressmentioning
confidence: 99%
“…Heavy metal is defined as “a metal with a density greater than 5 g cm –3 .” Of a total of 53 HMs that occur naturally, 17 are biologically available and are important for the ecosystem ( Alamri et al, 2018 ). For plants, Pb is a nonessential element, so it becomes toxic even at low concentrations.…”
Section: Toxicity Level and Mode Of Actionmentioning
confidence: 99%
“…There are important economic and ecological benefits from the use of microbes to adjust the concentration of HMs in the soil and to boost the ability of plants to cope with high concentrations of metals ( Alamri et al, 2018 ; Jin et al, 2018 ). The response of cereals to Pb toxicity can be improved by applying plant-associated microorganisms that promote growth and developmental physiology.…”
Section: Phytoremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that foliar applications of AsA could be used as a management practice to alleviate the water stress in young peach trees and improve their performance after rewatering [206]. In nonwoody plants, AsA foliar spraying efficiently mitigated the detrimental effects of water stress in maize [207] and wheat [208], and Pb toxicity-induced oxidative damage in wheat plants [209] and faba bean [210]. Asc foliar spraying increased tolerance to water deficit by reducing ROS levels and ROS-induced damage in pot marigold [211], increasing the resistance to salt stress and lipid peroxidation in tomato [212], and affecting millet growth and salinity resistance [213].…”
Section: The Effects Of Asa Applicationmentioning
confidence: 99%